Modulable and Highly Diastereoselective Carbometalations of Cyclopropenes. Issue 4 (12th December 2013) - Didier, Dorian; Delaye, Pierre‐Olivier; Simaan, Marwan; Island, Biana; Eppe, Guillaume; Eijsberg, Hendrik; Kleiner, Amir; Knochel, Paul; Marek, Ilan
Abstract The copper‐catalyzed carbomagnesiation reaction of cyclopropenyl esters 1 leads to various substituted cyclopropanes species 3 in good yields with very high diastereoselectivities. The reaction proceeds through a syn‐chelated carbomagnesiation reaction and could be extended to various cyclopropenylmethyl ester derivatives 5. The potential of this approach was illustrated by the preparation of two consecutive all‐carbon quaternary stereocenters. However, the carbometalation reaction needs to be performed at temperature ranging from −35 to −20 °C to avoid subsequent fragmentation reaction into stereodefined β, γ‐nonconjugated unsaturated esters 4. Alternatively, the carbocupration reaction with organocopper species could also be performed to leads to configurationally stable cyclopropyl copper species 2[Cu]. Additionally, when the Lewis acid character of the copper center is decreased (i.e., RCuCNLi), the reaction proceed with an anti‐selectivity. The diastereodivergent behavior of these organometallic species is of synthetic interest, since both diastereomers syn‐3 and anti‐3 can be obtained, at will, from the same precursor cyclopropenyl esters 1.